A Modified PWM Strategy With an Improved ANN Based MPPT Algorithm for Solar PV Fed NPC Inverter Driven Induction Motor Drives - Nazmul Islam Nahin (17949158) (2023)
The integration of solar photovoltaic (PV) arrays for induction motor drives (IMDs) has attained a lot of research interest due to the versatile applications of IMD including water pumping, cement industries, electric vehicles, and rolling mills etc. Multilevel inverters (MLIs) are a prominent solution for driving medium voltage induction motors (IMs) due to their superior performances over two-level voltage source inverters (VSIs). However, the power quality performance of MLI fed IMDs greatly depends on the pulse width modulation (PWM) strategy employed. Traditional PWM strategies for MLIs suffer from power quality problem such as lower order harmonics, high THD, unbalanced power loss distribution, high switching power loss, thermal instability and electromagnetic interference (EMI) problems. In this paper, a modified PWM strategy is proposed for a solar PV fed 3-level neutral point clamped (NPC) inverter driven IMD. The proposed PWM strategy introduces a new modulating signal with level shifted triangular carriers. The proposed modulating signal is formed by utilizing a $13^{th}$ harmonic signal and saturated balanced 3-phase sinusoidal signals. The proposed PWM technique is named as $13^{th}$ harmonic injected 60°-PWM (THISDPWM). The THISDPWM reduces the lower order harmonics contents, overall THD, and switching power losses of the NPC inverter compared to different existing PWM strategies. Apart from that, a robust artificial neutral network (ANN) based incremental conductance maximum power point tracking (MPPT) algorithm is also introduced to control the dc-link voltage of the PV fed NPC inverter driven IMD system. The presented ANN based dc-link controlled technique ensures stable dc-link voltage against wide range of PV parameters variation. All the simulation works are carried out in MATLAB/Simulink environment and a reduced scale laboratory prototype of the IMD is built and tested to validate the performance of the proposed THISDPWM technique. Other Information Published in: IEEE Access License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3291339